Bsm1 Gene polymorphism of the vitamin D receptor in breast cancer patients: influence of obesity and relevant drugs. (January 2017) - Haikal, Noha; El-Hussiny, Mona; Farouk, Omar; Abo Hashem, Ekbal
Abstract Breast cancer (BC) is a common cancer among women, especially in developing countries. Circulating serum 25-hydroxyvitamin D [25(OH)D] is the key factor that regulates tissue synthesis of the active form 1, 25- dihydroxyvitamin D [1, 25(OH)2 D]. 1, 25(OH)2 D has anticarcinogenic properties against breast cancer via binding to vitamin D receptors (VDRs). One of the common VDRs gene polymorphism which is located at the 3′ end ofVDR gene is the Bsm-I gene polymorphism (rs1544410). Certain VDRs polymorphisms are associated with obesity and show relation to breast cancer risk. The current study was conducted on 60 breast cancer females and 30 healthy control subjects of matched age. Total serum 25(OH) vitamin D was measured using enzyme-linked immunosorbent assay (ELISA) technique. Vitamin D receptor VDR–Bsm1 gene polymorphism was assessed by PCR/RFLP method. Levels of 25(OH) vitamin D were significantly decreased in total, overweight, and obese BC patients in comparison to control group (p = 0.002, <0.001, <0.001, respectively). Regarding Bsm-1 polymorphism, no significant differences were observed between BC patients and control subjects with no risk to develop BC. Bsm-1 gene polymorphism is not associated with breast cancer risk and this result is not affected by increased BMI. A protective effect is observed for [25(OH)D] and ionized calcium levels against BC development.